Implementasi dan Analisis Algoritma Binary Search - Putri, Rizyallatul Nurvita Meindika (Maliki Interdisciplinary Journal, 2025)
The Binary Search algorithm is an extremely efficient search method for finding elements within a sorted array. This research aims to analyze the basic concepts, implementation, and advantages of this algorithm compared to linear search methods. With a time complexity of O(log n), Binary Search significantly reduces the number of elements inspected in each iteration through its logarithmic approach. The implementation of this algorithm is demonstrated through programming languages, and a case study of searching for book titles in a digital library is used as a practical example. The analysis results show that Binary Search offers high efficiency, particularly in scenarios involving large, well-structured data sets. This knowledge will open up opportunities to develop faster, more efficient and more reliable software solutions in various application fields